No millipede endemics north of the Alps? DNA-Barcoding reveals Glomeris malmivaga Verhoeff, 1912 as a synonym of G. ornata Koch, 1847 (Diplopoda, Glomerida, Glomeridae) - Wesener, Thomas (Zootaxa, 2015)
In order to evaluate the status of the only species of pill millipede (Glomerida) endemic to Germany, Glomeris malmivaga Verhoeff, 1912, a DNA barcoding study based on the COI mitochondrial gene was conducted. Sequences of G. malmivaga were compared to those of G. ornata Koch, 1847 from Slovenia, of which the former was previously described as a variety of the latter before being elevated to subspecies- and, recently, species-rank. Included in the analysis were specimens of G. helvetica Verhoeff, 1894, also originally described as a variety of G. ornata, which was supposed to be closely related to G. malmivaga based on its morphology, as well as geographical proximity of occurrence. Additionally, G. valesiaca Rothenbühler, 1899, which occurs in sympatry and looks quite similar to G. helvetica was also sequenced for the first time and included in the study. Sequences of four widespread Glomeris species, all occurring in close proximity to G. malmivaga, G. marginata Villers, 1789, G. connexa Koch, 1847, G. klugii Brandt, 1833 and G. intermedia Latzel, 1884 were downloaded from Genbank and incorporated in the analysis. While G. helvetica and G. valesiaca were found to be clearly separate from G. ornata (11.8–14.6% p-distance), G. malmivaga is almost identical to the latter (0.5% p-distance), despite the large geographical distance between both species. Because of their great morphological and genetical similarity, G. malmivaga n. syn. is synonymised under G. ornata.